Logic and logics: on unadressed complaints of Leibniz and Quine - Camacho, Luis (2025)
Leibniz´s complaint in a short essay written at an uncertain date shows insatisfaction with the status of Logic in his time. If we have in mind the purpose of Logic as it is stated in Plato´s Phaedon , and the present-day separation between formal and informal Logic, the complaint is still valid in some respects in spite of the time elapsed. Quine´s complaint is even more obvious and valid: the proliferation of equivalent symbols in Logic is unnecesary and turns redundant many efforts in the discipline. Our research leads us to interesting conclusions on the relation between natural and formal languages.